Transformation of Social Interaction Patterns of the Young Generation in the Digital Age: An Analysis of the Influence of Social Media on Social Life and Local Culture - Suat, Hatty; Khairunnisa, Atikah; Rieuwpassa, Sarmalina; Lestari, Faradila Ishara (PT. Anagata Sembagi Education, 2025)
Advances in digital technology, particularly social media, have brought about fundamental changes in the social interaction patterns of the younger generation. These changes not only include the way young people communicate and interact, but also have an impact on the dynamics of social life and the preservation of local culture. This study aims to analyze how social media affects the social interaction patterns of the younger generation and its implications for social life and local culture. A qualitative approach was used in this research, with literature study methods and in-depth interviews with the target group consisting of teenagers and youth in various social environments. The results show that social media facilitates wider connectivity and accelerates information exchange, enabling young people to build social relationships without geographical boundaries. However, on the other hand, high reliance on digital interactions leads to less face-to-face communication, which can reduce the depth of interpersonal relationships and weaken social ties within local communities. Exposure to global culture through social media has the potential to shift local cultural identity, both in communication patterns, lifestyles, and social values. This phenomenon can lead to changes in the mindset and behavior of the younger generation who are more likely to adopt foreign cultures than maintain their own cultural heritage. However, social media can also act as a tool to strengthen and promote local culture if utilized with the right strategy. A balanced approach is needed between the utilization of social media and the preservation of local culture, both through digital education and policies that support cultural integration in the digital world